Relationship between hand-eye coordination and hand grip strength in elite taekwondo athletes - Hammad, R.; Youssef, L.; Hammad, S.; Neva, J.; Abu Baker, A.; Noirez, P.; Dabayebeh, I. M.; Djemai, H. (SportMont, 2024)
Hand-Eye Coordination (HEC) and Hand Grip Strength (HGS) are among the most important skills in Taekwondo. On a technical level, HEC reflects neuromuscular coordination ability which enables quick responses, and HGS reflects muscle strength which indicates the strength and overall health of the athletes. Combined together, HEC and HGS likely allow Taekwondo athletes to perform better. The aim of this study was to identify if there is a relationship between HEC and HGS in elite Taekwondo athletes. 166 elite Taekwondo athletes (141 males, 25 females) voluntarily participated in this study and were divided into two categories: seniors (age >17 years) and juniors (age =17 years). HEC was assessed by hand-eye coordination manual dexterity test (Lafayette, IN, US) and HGS was measured using a hand dynamometer (Takei, Niigata, Japan). The results revealed that no significant relationship was observed between HEC and HGS (p>0.05) in elite Taekwondo athletes. Despite the several strength and neuromuscular adaptations acquired during Taekwondo practice, HEC and HGS are not significantly correlated, and hence there is no relationship between HEC and HGS in elite Taekwondo athletes. The results obtained may benefit Taekwondo coaches and athletes in improving their training strategies.